Comparison of endoscopic healing and durability between infliximab originator and CT-P13 in pediatric patients with inflammatory bowel disease - Kim, Eun Sil; Choi, Sujin; Choe, Byung-Ho; Park, Sowon; Lee, Yeoun Joo; Sohn, Sang Jun; Kim, Soon Chul; Kang, Ki Soo; Lee, Kunsong; Shim, Jung Ok; Kim, Yu Bin; Hong, Suk Jin; et al. (Frontiers in Immunology, 2024)
Background and aims Favourable clinical data were published on the efficacy of CT-P13, the first biosimilar of infliximab (IFX), in pediatric inflammatory bowel disease (IBD); however, few studies have compared the effect on endoscopic healing (EH) and drug retention rate between the IFX originator and CT-P13. Therefore, we aimed to compare EH and the drug retention rate between the IFX originator and CT-P13. Methods Children with Crohn’s disease (CD) and ulcerative colitis (UC)/IBD-unclassified (IBD-U) at 22 medical centers were enrolled, with a retrospective review conducted at 1-year and last follow-up. Clinical remission, EH and drug retention rate were evaluated. Results We studied 416 pediatric patients with IBD: 77.4% had CD and 22.6% had UC/IBD-U. Among them, 255 (61.3%) received the IFX originator and 161 (38.7%) received CT-P13. No statistically significant differences were found between the IFX originator and CT-P13 in terms of corticosteroid-free remission and adverse events. At 1-year follow-up, EH rates were comparable between them (CD: P=0.902, UC: P=0.860). The estimated cumulative cessation rates were not significantly different between the two groups. In patients with CD, the drug retention rates were 66.1% in the IFX originator and 71.6% in the CT-P13 group at the maximum follow-up period (P >0.05). In patients with UC, the drug retention rates were 49.8% in the IFX originator and 56.3% in the CT-P13 group at the maximum follow-up period (P >0.05). Conclusions The IFX originator and CT-P13 demonstrated comparable therapeutic response including EH, clinical remission, drug retention rate and safety in pediatric IBD.